Can Social Health Insurance Improve Beneficiaries' Diets?—An Evaluation of China’s New Rural Cooperative Medical Scheme Based On A Difference-in-Differences Design - Chen, Qihui; Pei, Chunchen; Huang, Juerong; Tian, Guoqiang (Disease and Health: Research Developments Vol. 1, 2024)
Aims: This chapter evaluates the consumption-stimulation function of social health insurance programs from the perspective of food consumption and diet structure. China’s New Rural Cooperative Medical Scheme (NRCMS), launched in 2003, with data collected in 2000-2006 from a large-scale survey, was used as the focal program in the evaluation study. Study Design: The study undertakes a retrospective quantitative evaluation design. Exploiting temporal and spatial variations in the local implementation of the program, a difference-in-differences model was developed to estimate the effect of health insurance coverage on the insured’s diet diversity, overall diet balance, and nutrition intake. Data: A sample of 2,260 rural Chinese individuals of working age in the 2000, 2004, and 2006 waves of the China Nutrition and Health Survey (1989-2015) was used as the estimation sample. Methodology: Detailed information on survey respondents’ consumption of more than 1,500 food items was used to construct two diet-structure indicators to serve as the primary outcome variables of our difference-in-differences analyses: 1) diet-diversity score, a “variety-based” indicator that counts the number of food groups one consumes out of the set of foods recommended by the Chinese Nutrition Association; 2) diet-balance index, a more comprehensive and “balance-based” indicator which takes into account not only one’s diet diversity but also one’s under- and over-consumption of foods. Results: NRCMS enrollment significantly increased the insured’s nutrition intake (carbohydrate intake by 11.3%, protein intake by 8.6-9.3%, fat intake by 6.6-7.3%), diet diversity (by 0.3 out of 12 recommended food groups), and overall diet balance (by 2.7 points). Meanwhile, while program enrollment reduced the incidence of under-consumption of animal products and fruits, it raised that of over-consumption of grains. Conclusion: Social health insurance can stimulate the insured’s food consumption and increase their diet diversity, but it could also impose health risks by changing their diet structure in undesirable directions. More research is needed to 1) understand why these undesirable effects occur and 2) how the program can be modified to avoid these effects.